Hidden Water Balances. Strategies for an Ecosystemic Urbanism in the Vall Baixa of the Llobregat River - Crosas Armengol, Carles; Martí Elias, Joan (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
In the Barcelona Metropolitan Area, the Vall Baixa territory forms a discontinuous linear city modelled by the logics of geography and water. A historical perspective of the territorial and urban development of this area provides some interesting lessons about the relation between urban form, agriculture and water. Nevertheless, the introduction of modern mobility infrastructures since 1970 and some subsequent invasive urban developments have caused substantial changes in the “liquid” balances of this territory. An analysis of the current situation suggests some strategies for continuing to enhance the water cycle in this metropolitan fragment, which has recently undergone successful recovery of the riverbed. Through combined strategies of artificialization of water systems and naturalization of the landscape, the importance of “hidden” water that nourishes the aquifer is highlighted as a fundamental element that should guide some urban projects to upgrade the territorial metabolism.
Keywords: Vall Baixa; Llobregat; Territorial Metabolism; Water Cycle; Urban Projects